Integration of Civil Registration and Vital Statistics and Identity Management Systems : Botswana Success Story - Republic of Botswana (World Bank, Washington, DC, 2017)
The initiative of a case study on Botswana’s successful integration of civil and identification registers comes against a backdrop of major continental and global efforts to accelerate improvement in the area of civil registration. The national identification system (NIS) is linked with other government systems such as the elections system, the social benefits registration system (SOBERS), the government payroll, the transport system, and others to facilitate service delivery because a person’s identity serves as a gateway for accessing services. In addition, through this link the NIS is updated in real-time when a death occurs and the status of the registered citizen is automatically changed from live to deceased, and this update is imported to all other interfaced government systems in real-time. Civil registration is a credible source from which vital statistics in Botswana can be generated and was used previously to generate population reports. The creation of one department to provide civil and national registration headed by a single Registrar for both civil and national registration brought about benefits of synchronization of processes and immediate decision-making. Furthermore, having an institutional framework in place facilitates the smooth implementation of civil registration and vital statistics (CRVS) and identity management (ID-M) through a network of offices strategically placed across the country to ensure that services are brought closer to the people.